Completion of Adjuvant Radiation Therapy Among Women With Breast Cancer - Srokowski, Tomasz P. (2008)
BACKGROUND: Optimal treatment for breast cancer often involves lengthy multimodality care including 5 to 6 weeks of radiotherapy, but few studies have evaluated adherence to radiotherapy outside the context of a therapeutic clinical trial. METHODS: Using a SEER-Medicare database, the authors identified women age 66 years or older with Stage I to III breast cancer diagnosed between 1992 and 2002. They evaluated rates of completion of radiotherapy, defined as a minimum of 25 sessions. Multivariate logistic regression analyses were performed to determine factors associated with completion of radiotherapy, and Cox multivariate models were used to determine the impact of radiotherapy completion on local recurrence. RESULTS: Some 24,510 patients were included in the study. Eighty-seven percent of patients completed 25 or more radiotherapy sessions. In multivariate logistic regression models, mastectomy (HR 1.26, 95% CI 1.10-1.43), hospitalization during treatment (2.87, 2.49-3.31), earlier year of diagnosis, and black race (1.36, 1.14-1.63) were associated with increased risk of non-completion of radiotherapy. Among 21,269 patients treated with breast conservation, incomplete radiotherapy was associated with higher risk of local recurrence. A total of 98.7% of patients who did not complete radiation therapy were free of recurrence at 5 years vs. 97.5% of patients who completed radiation therapy (HR 1.46, CI 1.09-1.95). CONCLUSION: This study demonstrates relatively high rates of completion of radiation therapy among a population of older woman with breast cancer. However, those who did not complete a full course of radiotherapy had small but statistically significant higher risk of breast cancer recurrence. Future efforts should focus on intervening with women at high risk of not receiving adjuvant radiotherapy and increasing rates of radiotherapy completion.